Development of bioactive glass based scaffolds for controlled antibiotic release in bone tissue engineering via biodegradable polymer layered coating - Nooeaid, Patcharakamon (2014)
Highly porous 45S5 Bioglass®-based scaffolds coated with two polymer layers were fabricated to serve as a multifunctional device with controlled drug release capability for bone regeneration applications. An interior poly(d,l-lactide)/poly(ethylene glycol)-(polypropylene glycol)-poly(ethylene glycol) triblock copolymer (Pluronic P123) coating improved the mechanical stability of Bioglass-based scaffolds, while an exterior natural polymer (alginate or gelatin) coating served as an antibiotic drug carrier. The results showed improved mechanical properties of Bioglass-based scaffolds by the bilayer polymer coating. In addition, hydrochloride tetracycline loaded in either alginate or gelatin coatings was released rapidly at the initial stage (∼1 h), while the released rate subsequently decreased and was sustained for 14 days in phosphate buffered saline. Therefore, these layered polymer coated scaffolds exhibit attractive characteristics in terms of improved mechanical properties and controlled drug release, simultaneously with the added advantage that the drug release rate is decoupled from the intrinsic scaffold Bioglass degradation mechanism. The layered polymer coated scaffolds are of interest for drug-delivery enhanced bone regeneration applications.